2020
DOI: 10.15690/pf.v17i3.2127
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Emotional Disorders in Children during the COVID-19 Epidemic

Abstract: This article has been published in English before [1].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 20 publications
2
19
0
2
Order By: Relevance
“…Public health organizations and mental health experts have also acknowledged the potential adverse psychological effects of quarantine on children and adolescents [e.g., (11)(12)(13)]. Children have unique and specific needs that are disturbed by COVID-19 quarantine that includes not only home confinement but the inability to go to school and interact with peers and teachers (14).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Public health organizations and mental health experts have also acknowledged the potential adverse psychological effects of quarantine on children and adolescents [e.g., (11)(12)(13)]. Children have unique and specific needs that are disturbed by COVID-19 quarantine that includes not only home confinement but the inability to go to school and interact with peers and teachers (14).…”
Section: Introductionmentioning
confidence: 99%
“…One of the few studies concerning this population (10) found that children who had been quarantined exhibited increased rates of posttraumatic stress symptoms compared with children who were not quarantined, indicating that home confinement can be traumatizing to a significant number of children. A recent study conducted in China in February 2020 with children aged 3-18 years concluded that the most frequent psychological and behavioral problems included clinginess, distraction, irritability, and fear of asking questions about the outbreak (12).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…After a long time when the pandemic is over, they could experience such problems as separating from parents, socialization and adaptation etc. Even though this effect varies depending on the socio-cultural and socioeconomic condition where children are in, effects of these negative experiences in childhood could emerge in the coming periods (Boyraz & Legros, 2020;Çaykuş & Mutlu Çaykuş, 2020;Dalton et al, 2020;Demir Öztürk et al, 2020;Dubey et al, 2020;Ghosh et al, 2020;Guan et al, 2020;Jiao et al, 2020;United Nations, 2020).…”
Section: Introductionmentioning
confidence: 99%